The Reform of Civic Politics in Thai Local Politics and Administration - suvanamongkol, pathan (King Prajadhipok’s Institute Journal, 2020)
The Reform of Civic Politics in Thai Local Politics and Administration has three objectives: (1) to study the role of civic politics in local politics and administration;(2) to study the main problems of civic politics in local politics and administration since 1997 to the present (2015); and (3) to recommend ways to promote a greater role for civic politics in local politics and administration. This research was primarily qualitative with the support of quantitative research. The sample population consisted of members of sub-district organization councils and political development councils. Descriptive analysis and percentage were used to analyze the data. The study found that the main problems of civic politics in Thai local politics and administration were both policy problems and practical problemsthat resulted from external and internal factors of civic politics. Examples of problems included lack of clear public policy on civic politics, lack of management skill, and lack of strong leadership. The researcher proposed both policy and practical recommendations to enhance strong civic politics in local politics and administration. The government should propose laws to promote people’s participation in public policy at national and local level, a “civic council” should be created to provide counseling and monitor local authorities’ and public agencies’ performance of their duties, and participatory budgeting in local authorities should be promoted.